Harvard Project Zero: A Personal History - Gardner, Howard (Uaricha, 2016)
Rationale: The re-launching of a course focused on Harvard Project Zero served as a stimulus for me to set down the history of Project Zero, with particular attention placed on its early history. And so, on Tuesday, January 29th, 2013, I spoke offthe- cuff on this topic for over an hour. Those remarks were video-recorded and the sound quality is quite good. So, an oral version of much of this history is available for those who’d rather watch and listen. I’ve provided a written account for three reasons: 1) It is lengthier and somewhat more authoritative; 2) In the event that I get hit by a bus, it would be useful to have such an account available; 3) Prompted by this account, I’d like to invite others to provide their own recollections. (See the list at the end of this essay). Of course, there are at least a score of other persons who would have recollections of the early days, even though they are no longer working at Project Zero.there are several dozen) or particular investigators (of which there are also dozens). Many of these are described in the documentation about Project Zero available on the web and in publications about Project Zero or by the investigators themselves (http://www.pz.harvard.edu/about-projectzero. php). Had I gone into specific projects, this document would be very lengthy, and likely to be read even less than this one.